Individual and Colony Level Foraging Decisions of Bumble Bees and Honey Bees in Relation to Balancing of Nutrient Needs - Hendriksma, Harmen P.; Toth, Amy L.; Shafir, Sharoni (Frontiers in Ecology and Evolution, 2019)
Foraging decisions of social animals occur in the context of social groups, and thus may be subject to considerations of not only an individual’s nutritional state and nutrient input, but those of the social group in which they live. In eusocial insects, which live in colonies containing workers that forage for food that is mostly consumed by others, foraging decisions that reflect colony needs may also be considered at both the colony and individual level. If colony energy balance is perturbed, is the counteracting response occurring on the group level (a change in division of labor) or on the individual level (a change in individual foraging choices)? To address this, colony and individual level foraging behaviors were observed in two species of eusocial bees: the highly social honey bee Apis mellifera and the primitively eusocial bumble bee Bombus terrestris. After manipulations of protein (P) and carbohydrate (C) stores in colonies of both species, there were changes in multiple different behavioral responses including colony level (number of foragers, allocation to nectar and pollen foraging, nutrient mass foraged) and individual level (P and C concentration preference and loading during foraging). These results suggest both honey bee and bumble bee colonies balance nutrient needs through a combination of both colony level shifts in foraging allocation, as well as slight modulation of individual nutrient preferences. This study also uncovered colony level differences between the two bee species; honeybees balanced P intake while bumble bees balanced C intake. These patterns may reflect differences in life history traits such as perenniality and hoarding, traits that are developed in more highly social species. Overall, this study highlights the importance of considering both group and individual level behavioral responses in foraging decisions in social animals.